2007
DOI: 10.1007/s11270-007-9468-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities in Long-Term Heavy Metal Contaminated Ombrotrophic Peats

Abstract: High concentrations of heavy metals are known to be toxic to many soil organisms. The effects of long-term exposure to lower levels of metals on the soil microbial community are, however, less well understood. The southern Pennines of the U.K. are characterised by expanses of ombrotrophic peat soils that have experienced deposition of high levels of heavy metals since the mid to late 1800s. Concentrations of metals in the peat remain high but the effect of the contamination on the in-situ microbial communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…Further, the research conducted here supports previous studies (Li et al 2006;Linton et al 2007;Sullivan et al 2013b;Yang et al 2013) that have shown that metal availability is important when considering the impacts of heavy metals on microbial community structure. While broad α-diversity metrics appear to be somewhat unaffected, β-diversity was significant between USA and PRC locations, and individual taxonomic groups correlate strongly with the presence of available heavy metals.…”
Section: Impact Of Available Metal On Microbial Otussupporting
confidence: 89%
See 1 more Smart Citation
“…Further, the research conducted here supports previous studies (Li et al 2006;Linton et al 2007;Sullivan et al 2013b;Yang et al 2013) that have shown that metal availability is important when considering the impacts of heavy metals on microbial community structure. While broad α-diversity metrics appear to be somewhat unaffected, β-diversity was significant between USA and PRC locations, and individual taxonomic groups correlate strongly with the presence of available heavy metals.…”
Section: Impact Of Available Metal On Microbial Otussupporting
confidence: 89%
“…Generally, sites had low levels of available metals, other than available Zn. Several studies have previously found strong correlations between microbial communities and bioavailable metal concentrations (Li et al 2006;Linton et al 2007;Sullivan et al 2013b). Thus, total metal concentration could be viewed as potential impact to biological communities (should the metals become re-available), while bioavailable metal concentration directly influences the biota at that given time.…”
Section: Community Comparison Of Aquatic Sedimentsmentioning
confidence: 99%
“…Ellis et al (2003), however, did not see any difference in bacterial communities between metal contaminated and pristine soils using this molecular technique despite finding significantly different community profiles using culture dependent techniques. Linton et al (2007) likewise reported no significant difference in the number of dominant species identified, although marked different in species composition was seen.…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge) and Temperatumentioning
confidence: 90%
“…To a lesser extent the same phenomenon is observed for the bottom layers where an increase in Zn concentration can also be seen. Zn is rather weakly bound to organic matter (Linton et al 2007) thus its mobility in peat is expected to be higher than that of Pb. The visibly higher Zn content was observed down to 40-50 cm while higher Pb concentration reached the 30-40 cm layer.…”
Section: Discussionmentioning
confidence: 99%